‘Don’t talk to them!’ on the promise and the pitfalls of liaison policing at COP26 - Gorringe, Hugo (Policing and society, 2024)
Initially introduced and hailed as means of offering more democratic and facilitative policing, but increasingly subject to question by protestors, Police Liaison Teams (PLTs) are one of the primary tactical options used by Public Order Police in the UK. This paper will analyse the deployment of PLTs over the 14 days of the global COP26 summit in Glasgow in 2021. The police plan for the event emphasised Human Rights, dialogue and facilitation, but some protest groups accused PLTs of ‘intelligence-gathering’ and urged activists not to speak to them. This paper draws on participant observation and interviews with both police and protestors to analyse the deployment of PLTs at the summit and consider why some groups chose not to engage with the liaison officers. Responding to calls for more evidence-based analyses of PLT deployment, we highlight the difficulties of police-protestor liaison at a Global Summit and outline why protest groups might choose not to engage.